Political Change in Post-Communist Slovakia and Croatia: From Nationalist to Europeanist - Fisher, S. author. aut Link
X, 263 p.
Keywords: Revealing how the quest for independence and challenges of democratization created a contest between nationalists and Europeanists, two powerful forces in domestic politics, after the collapse of communism, Fisher sheds light on the nationalism and post-communist transitions.